Existe-t-il un ancrage spatial des minorités chrétiennes en Asie centrale ?Le poids du passé russo-soviétique - Sébastien Peyrouse (Revue des Mondes Musulmans et de la Méditerranée)
The five Central Asia Moslem Republics, born from the former USSR in 1991, are interesting examples for the problematics studied here: they invite to raise again the religious minority question in Islamic countries but in a different way from the usual diagram on the question. These Republics show that some Moslem countries don’t have any specific legislation towards religious minorities; communities are then more divided according to nationalities lines than to strictly religious criteria. The space retains the memory of the brutal urban transformations required by the Soviet power, which has denied all expressions of faith. Indeed, both religion and urbanism in Central Asia cannot be understood without referring to the Russo-Soviet bequest: populations of the five republics live today in an essentially Europeanised urban environment, marked by the presence of the non-Moslem populations. Space is then little perceived as a community differentiation factor.